Silver-catalyzed carboxylative cyclization of primary propargyl alcohols with CO2 - Dabral, Saumya; Schießl, Jasmin; Hashmi, A. Stephen K. (Organic letters, 2019)
By using silver complexes with bulky ligands such as DavePhos or N-heterocyclic carbenes, propargylic alcohols are smoothly converted with CO2 into a unique class of unexplored cyclic alkylidene carbonates. These systems, for the first time, also achieve the direct carboxylative cyclization of primary propargylic alcohols. The silver-DavePhos catalyst is further applied for the bis-carboxylative cyclization of primary propargyl derivatives, thereby providing an effective route to a series of previously inaccessible and industrially relevant α-alkylidene cyclic carbonates.
Im Titel ist „2“ tiefgestellt
Gesehen am 09.05.2019